Cover Picture: Plasma Process. Polym. 2/2021. Issue 2 (8th February 2021) - Malekzad, Hediyeh; Gallingani, Tommaso; Barletta, Federica; Gherardi, Matteo; Colombo, Vittorio; Duday, David
Abstract : Cover Picture : A Corona plasma jet was moved along the substrate with a constant speed and an increasing oxygen amount while maintaining constant the other deposition parameters including hexamethyldisiloxane flow rate. The gradual incorporation of oxygen into siloxane‐based coating led to the formation of wettability gradient along the coating primarily as a result of increase in surface polar groups (chemistry effect) and next due to the surface roughness variation (physical effect). Further details can be found in the article by Hediyeh Malekzad, Tommaso Gallingani, Federica Barletta, Matteo Gherardi, Vittorio Colombo, and David Duday (e2000044 ).